A cross sectional study of 1000 lower segment cesarean section in obstetrics and gynecology department of P. D. U Medical College, Rajkot, Gujarat, India - Chavda, Dolly; Goswam, Kamal; Dudhrejiya, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Though WHO recommends a rate of 10-15% caesarean section for a given hospital, there has been a rising trend worldwide. We estimated the recent incidence of caesarean section in Obstetrics and Gynecology Department, P.D.U. Medical College, Rajkot (Gujarat and correlated these rates with the socioeconomic, demographic, and health variables. Methods: We have studied 1000 cases of lower segment caesarean section (cross sectional study) at Obstetrics and Gynecology Department, P.D.U Medical College, Rajkot (Gujarat) to find out rate of caesarean section, common maternal and fetal indication and complications of lower segment caesarean section. Results: Caesarean section rate of the present study is 19.9%. Most common indication of LSCS was scarred uterus 39.9%.followed by fetal distress 19.1%, malpresentation 18.6%, and failed induction 7.3%. Maternal morbidities and mortalities in emergency LSCS in compare to elective LSCS. Analysis based on Robson’s ten-group showed that group 5 (Previous CS, single cephalic,>37 weeks) made the greatest contribution to total CS rate. Conclusions: Scientific advances, social and cultural changes, and medico legal considerations seem to be the main reasons for the increased acceptability of caesarean sections. The decision to perform a C-section delivery must be chosen carefully and should not be profit oriented. There is a possibility of keeping the rate to minimum by reducing number of primary caesarean sections, by proper counseling of the patients, proper monitoring and patience.